The Effect of Color Perception on Short-Term Memory: The Effect of Color Perception on Short-Term Memory - Winda Sri Harianti; Nurul Khaerani Syani; Soraya Dian Pangestika Purnawan; Nelvia Syafitri; Cahya Hemas Pertiwi Eksiareh; Muhammad Hafizh Maulana; Megahputri, Adlina Windya; Hazhira Qudsyi (Journal of Research and Measurement in Psychology: JPPP, 2021)
Memory is very necessary on daily life, especially in learning. Likewise as color, which has an effect on cognitive system that can help increasing individuals’ attention level. This research mainly focused to explore the effect of color on short-term memory. Research design that we used is Randomized Pretest-Posttest Control Group Design with 16 subjects that equally divided into experiment group (n=8) and control group (n=8). Control group was asked to remember animals pictures with black and white color series meanwhile experiment group with colorful pictures. The subjects of this research were 19-23 years old women that is a college student and is not having or experiencing color blindness. The data was analyzed by using Anava Mixed Design for examine the hypothesis. The result showed that our hypothesis was denied because there is no effect of color on short-term memory with F = 0.324 and p = 0.578 (p > 0.05). Therefore, the result, procedure and treatment process will be discussed further in this study.